PERANAN DINAS PENDAPATAN DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH MELALUI PAJAK BUMI DAN BANGUNAN DI KOTA JAMBI - Nuraini Nuraini (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
This research is to know the role of the Department of Revenue in the Area increase revenue through Tax collection of Native Earth and buildings in the town of Jambi, what are the obstacles faced and the efforts made in improving the Region's Revenue Service Income Tax through the Native Earth and buildings in the town of Jambi.Regional Income Agency was instrumental in the success of the poll Taxes of the Earth and buildings in the city of Jambi exceeded targets that have been set previously.The achievement earned Income Tax collection in the Department of Earth and Building of the role and cooperation with districts and Villages that existed in the town of Jambi.Key words: role, income, region, tax